TINJAUAN YURIDIS TERHADAP ADOPSI ANAK WARGA NEGARA INDONESIA OLEH WARGA NEGARA ASING - Margaritha Rami Ndoen; Febi Meliana Ingratubun (Fakultas Hukum Univesitas Kristen Indonesia Paulus, 2021)
The adoption of Indonesian children by foreigners is one of the child protection efforts aimed at protecting children and making them happy by having a family that protects, educates, and provides love. Couples who do not have children or descendants usually adopt children (adoption). This study aims to find out how the legal protection for Indonesian children adopted by foreigners is, and what the legal consequences are. This type of research is normative research, secondary data collection techniques consisting of primary legal materials and secondary legal materials, the data obtained are processed using qualitative analysis. The results of the study indicate that the form of legal protection for Indonesian children adopted by foreign nationals consists of 2 (two) kinds of legal protection, namely preventive protection is carried out to prevent disputes as listed in several laws. Meanwhile, repressive protection is carried out after the occurrence of disputes, namely those listed in Law No.39/1999 concering Human Rights, Law No.23/2002 concering Child Protection, and Law No.12/2006 concering Citizenship.